Rereading Ibn Khaldun’s Asabiyyah as a Critique of the Crisis of Modern Civilisation - Amri Saputra; Mahmud Arif (Al-Hikmah: International Journal of Islamic Studies, 2025)
This article revisits the concept of asabiyyah in Ibn Khaldun’s thought as a foundation for critiquing the crisis of modern civilisation. In a global context marked by material progress, social fragmentation, and the erosion of solidarity, the idea of asabiyyah offers a moral and social framework relevant to understanding the dynamics of contemporary society. This study employs a qualitative approach using the historical-philosophical hermeneutic method to interpret the text of Al-Muqaddimah and relate it to modern social problems. The analysis reveals that asabiyyah, which originally arose from the Bedouin tribal way of life as a force of solidarity and social loyalty, represents a moral energy that gives birth to civilisation and political power. However, asabiyyah tends to weaken when society becomes immersed in luxury and egoism. In the modern context, this concept can be reread as a call to build a new form of solidarity grounded in values, ethics, and social responsibility. The study concludes that Ibn Khaldun’s thought remains relevant as a critical reflection on the challenges of social disintegration and moral crisis in modern civilisation.